Herd behavior in Vietnam's stock market: Impacts of COVID-19 - Phan Hong Mai; Le Thi Nhu Quynh; Vu Duc Hieu Dam; Manh Son Tran; Truong Thi Hoai Linh; Quoc Anh Le (Cogent Economics & Finance, 2023)
This paper investigates herd behavior in frontier Vietnamese stock markets under the impacts of COVID-19. Using models with two measures of return dispersions, we find that herd behavior does not exist in the three stock markets in extreme movements but in normal market conditions. Herding is more severe in two stock exchanges, HoSE and HNX, than in the OTC market UpCOM. Intentional herding is the main form and has been more intense in HoSE and HNX since the COVID-19 outbreak, while it is mainly significant in UpCOM in the pre-pandemic period. There is strong evidence of significant intentional herding on days of high volatility in UpCOM and HNX for all the timeframes, while considerable spurious herding on days with low volatility is found in UpCOM and HNX for all the examined periods except for the pandemic one. The evidence that herding was more pronounced during high volatility days in HoSE was relatively weak overall. Finally, pandemic uncertainty or government responses do not affect heightening or mitigating herd behavior, respectively.
Keywords: 330; COVID-19; herd behavior; Vietnam